Analisis Sudut Mata Potong Utama Pahat HSS dan Kedalaman Pemakanan Terhadap Kesilindrisan Baja ST 60 Pada Proses Bubut Memanjang - Frans Robert Bethony, Robert Bethony; Martina pineng; Christof Geraldi Simon (INTEK: Jurnal Penelitian, 2024)
This study aims to analyze the main cutting edge angle of HSS (high speed steel) chisel and the depth of cut on the cylindricity of ST 60 steel workpiece in the longitudinal turning process. The material used is ST 60 steel with a specimen length of 200 mm and a diameter of 30 mm and turned along 200 mm using variations of the main cutting edge angle, Kr (30, 45, 60, 90o) and the depth of cut, a (0.5; 1; 1.5; 2.0 mm) and other variables are set at constant conditions. Based on the results of this study, it can be concluded that the variation of the SS chisel cutting angle in the turning process produces an average total cylindricity value at a cutting angle of Kr 30o = 0.95 mm, Kr: 45o = 0.65 mm, Kr: 60o = 0.45 mm in other words, it can be concluded that the optimal cylindricity value occurs at a cutting angle of 90o = 0.15 mm. While the average cylindricity value at a cutting depth of a: 0.5 mm = 0.25 mm, a: 1 mm = 0.35 mm, a: 1.5 mm = 0.55 mm, a: 2.0 = 0.60 in other words that the optimal total cylindricity value is obtained at a cutting depth of 0.5 mm.